Pengaruh Brand Ambassador, Brand Image, Harga,Scarlett Whitening TerhadapKeputusan Pembelian (Studi Kasus Pada Remaja Pengguna Scarlett whitening di Kota Sumenep - Evi Onalisa; Muhammad Ridwan Basalamah; Eris Dianawati (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThis study aims to determine the effect of Brand Ambassador, Brand Image, Scarlett Whitening Price on purchasing decisions of Scarlett Whitening Brand products. The location of this research was carried out on teenagers in Sumenep City who became consumers of Scarlett Whitening products. This research is a quantitative research. This study used a case study method where data were obtained by distributing questionnaires to adolescents in Sumenep City who were selected by purposive sampling. Determination of the number of samples using the Ferdinand formula and the results obtained were 80 respondents. Data were analyzed using multiple linear regression test. Based on the results of data analysis, the results of the F test indicate that Brand Ambassador, Brand Image, Price have a significant and positive effect on purchasing decisions for Scarlett Whitening. Furthermore, the results of the t test show that Brand Ambassador, Brand Image, Price partially have a significant and positive effect on purchasing decisions for Scarlett whitening. Keywords: Purchase Decision, Brand Ambassador, Brand Image, Price